INOVASI PENDAYAGUNAAN ZAKAT PRODUKTIF DALAM PEMBERDAYAAN MUSTAHIQ: ANALISIS TEORI DIFUSI INOVASI ROGERS DAN PERSPEKTIF EKONOMI ISLAM M. UMER CHAPRA - Nur Mahmudah El Madja; Ashif Jauhar Winarto (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2026)
This study aims to analyze innovation in the productive utilization of zakat for mustahiq empowerment through Rogers’ diffusion of innovation theory and M. Umer Chapra’s Islamic economic perspective. It employs library research by examining primary sources, particularly Rogers’ and Chapra’s works, and secondary sources consisting of scholarly articles, books, and academic documents related to productive zakat, mustahiq empowerment, innovation diffusion, and Islamic economics. The data are analyzed through content analysis involving systematic reading, thematic classification, conceptual interpretation, and conclusion drawing. The findings reveal that productive zakat constitutes a socio-economic innovation that transforms zakat distribution from consumptive assistance into productive empowerment through business capital, mentoring, skill development, and capacity building for mustahiq. Within Rogers’ framework, the adoption process of productive zakat can be understood through adopter categories, namely innovators, early adopters, early majority, late majority, and laggards. Its acceptance is also shaped by five innovation attributes: relative advantage, compatibility, complexity, trialability, and observability. Mustahiq are more likely to adopt productive zakat when the program is perceived as beneficial, relevant to their needs, understandable, trialable, and able to demonstrate visible outcomes. From Chapra’s perspective, productive zakat aligns with the objectives of Islamic economics by promoting distributive justice, public welfare, falah, and hayat tayyibah. Thus, productive zakat functions not only as a wealth distribution mechanism but also as an empowerment strategy that balances material and spiritual well-being. This study emphasizes the need for adaptive, participatory, and sustainable zakat governance to enable mustahiq to achieve economic independence in a more inclusive and measurable manner